2008
DOI: 10.1111/j.1742-4658.2008.06475.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive decrease of phosphocreatine, creatine and creatine kinase in skeletal muscle upon transformation to sarcoma

Abstract: In biological systems, ATP is the universal energy currency. Excitable cells and tissues, such as skeletal and cardiac muscle, brain, photoreceptor cells, spermatozoa and electrocytes all depend on the immediate availability of vast amounts of energy that may be used in a pulsed or fluctuating manner [1,2]. Because the adenylate pool and the ATP : ADP ratio are key regulators influencing many fundamental metabolic In vertebrates, phosphocreatine and ATP are continuously interconverted by the reversible reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…The fact that creatine supplementation restored the impaired creatine-CK system in tumor cells led the authors to surmise that inhibition of AGAT and/or GAMT, which is thought to support cancer cell metabolism by contributing to polyamine and methionine synthesis, as shown by Locasale (2013), may be one of the reasons for the anti-cancer effects of creatine. The data reported by Campos Ferraz et al (2016) are in accord with similar data by Patra et al (2008), and suggest a potential therapeutic effect of creatine for the treatment of cancer (Pal et al 2016). The latter authors present evidence that creatine supplementation should be viewed as an adjuvant therapeutic intervention together with methylglyoxal (MG), a long-known anti-cancer agent.…”
Section: Creatine and Cancersupporting
confidence: 63%
“…The fact that creatine supplementation restored the impaired creatine-CK system in tumor cells led the authors to surmise that inhibition of AGAT and/or GAMT, which is thought to support cancer cell metabolism by contributing to polyamine and methionine synthesis, as shown by Locasale (2013), may be one of the reasons for the anti-cancer effects of creatine. The data reported by Campos Ferraz et al (2016) are in accord with similar data by Patra et al (2008), and suggest a potential therapeutic effect of creatine for the treatment of cancer (Pal et al 2016). The latter authors present evidence that creatine supplementation should be viewed as an adjuvant therapeutic intervention together with methylglyoxal (MG), a long-known anti-cancer agent.…”
Section: Creatine and Cancersupporting
confidence: 63%
“…The histological cross sections showed that upon transformation to sarcoma, the muscle tissue lost the muscle-specific phenotypes. The fiber-like nature of the skeletal muscle gradually disappeared as tumor development advanced, and the tissue became a mass of unorganized cells with no evidence of the presence of myofibres [7]. These observations suggested that the malignant transformation involved severe degradation of the muscle fibers.…”
Section: Introductionmentioning
confidence: 64%
“…Appropriate measures were taken to minimize the pain and discomfort to the animals. Sarcoma was induced as described earlier with 3MC in the hind legs of 45-day old Swiss albino female mice with a body weight of 20-22 g [7]. A stock solution of 3MC was prepared by dissolving 2 mg per 1 ml of hot olive oil, and cooling to room temperature.…”
Section: Growth Of Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial findings suggest that Cr, PCr and CK levels decrease as malignancy progresses. Concentrations of all these proteins can reach very low levels in the final stages of sarcoma development (Patra et al 2008). …”
Section: Resultsmentioning
confidence: 99%